Part of the Landscape - Treep, Lucy (Architectural History Aotearoa, 2022)
In 1969, Lincoln College (later University) opened a two-year postgraduate course in Landscape Architecture, the first of its kind in New Zealand. It was described as "for those who seek employment as professional landscape designers in private consulting practice or as members of planning teams in departments concerned with major engineering projects, highways, forestry, conservation and large-scale agricultural development." The college was seen to actively encourage women into the profession and from the first days of the course at Lincoln, women were part of the landscape. On March 3, 1969, Emily Mulligan was one of five founder students attending the first lecture of this new course. After Mulligan graduated in 1971, she was joined, in 1974, by Di Lucas, Diane Menzies and Esmae Sage, and not long after then, women started to regularly fill about half of each Landscape Architecture class. In comparison, the first woman student at the Auckland College School of Architecture, Laura Cassels-Browne, enrolled in 1926, nine years after the establishment of the school. The first woman graduate of the School of Architecture was Merle Greenwood in 1933, 16 years after the school’s establishment. Even in the 1960s and 70s women architecture students (who still made up small numbers) reported feeling uncertain of their welcome into the profession. Drawing on conversation with Emily Mulligan (now Williams), this paper will explore the nature of the landscape course at Lincoln, in what ways women students were encouraged in its early days, and the relationship of the course with the wider profession.